#TherapistsConnect: Our voices are stronger together. (7th December 2020) - Blundell, Peter
Abstract: This paper explores therapists' use of social media, including the author's reflections about the potential risks and benefits to therapists, and their work. These reflections are discussed in the context of the author's own social media use, as a therapist, which includes establishing #TherapistsConnect, an online community of therapists from around the world. Therapists' use of social media and their online presence can be part of a broader political process, which can help address issues such as therapist isolation, and challenging harmful narratives around therapy. The author argues for the importance of reflective practice when engaging with others on social media, and establishing an online presence as a therapist.